Effects of hydrostatic pressure on the martensitic phase transformation, thermal conduction and thermodynamic parameters of Cu-13 wt.% Al-4 wt.% Ni shape memory alloy - Zengin, R; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2003)
Effects of hydrostatic pressure on the martensitic phase transformation, thermal conduction and thermodynamic parameters of Cu-13 wt.% Al-4 wt.% Ni alloy have been investigated. The pressure dependence of M-S, M-f; A(s) and A(f) temperatures are interpreted in the frame of the study. The pressure dependence of the dissipative energy terms of the martensitic and reverse transformation has been separated and analyzed. It is found that the transformation temperatures of the shape memory alloy increase with applied stress. The thermal conductivity of the alloy was measured as a function of pressure. The thermodynamic parameters such as enthalpies, entropy and specific heat capacity of the alloy were determined. (C) 2003 Elsevier Science B.V All rights reserved.
Keywords: shape memory; thermal conduction; heat capacity